An infant with ring 17 chromosome and unusual dermatoglyphs: a new syndrome?. Issue 3 (June 1981) - Carpenter, N J; Leichtman, L G; Stamper, S; Say, B
Abstract : A case of ring 17 chromosome in a 5-month-old male infant is investigated and compared with five previously reported cases. The findings commonly observed in these patients include mental and motor retardation, seizures, short stature, muscular hypotonia, and microcephaly among others. Dermatoglyphic studies showed an increased number of ulnar loops. More interestingly, bilateral transverse hypothenar creases were noted. Two of the reported cases also had unspecified genital abnormalities. The variation in clinical findings among these patients may be explained by a difference in the breakpoints on chromosome 17.